2014
DOI: 10.6065/apem.2014.19.2.108
|View full text |Cite
|
Sign up to set email alerts
|

A Korean boy with 46,XX testicular disorder of sex development caused bySOX9duplication

Abstract: The 46,XX testicular disorder of sex development (DSD), also known as 46,XX male syndrome, is a rare form of DSD and clinical phenotype shows complete sex reversal from female to male. The sex-determining region Y (SRY) gene can be identified in most 46,XX testicular DSD patients; however, approximately 20% of patients with 46,XX testicular DSD are SRY-negative. The SRY-box 9 (SOX9) gene has several important functions during testis development and differentiation in males, and overexpression of SOX9 leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
1
16
0
1
Order By: Relevance
“…Sox9 is a direct target of SRY and has been shown to play a pivotal role in male sexual development. Ablation of Sox9 in humans [12,13] and mice [14][15][16] causes male-to-female phenotypic sex reversal while Sox9 gain-of-function, such as duplication of the SOX9 locus in humans [17,18] and Sryindependent upregulation of Sox9 in the fetal gonadal ridges of Wt1-Sox9 transgenic mice, causes testis formation in XX individuals [19]. The role of Sox9 in sex determination has mostly been studied in the context of two X chromosomes and focused on the period during fetal development when the sex determination takes place.…”
Section: Introductionmentioning
confidence: 99%
“…Sox9 is a direct target of SRY and has been shown to play a pivotal role in male sexual development. Ablation of Sox9 in humans [12,13] and mice [14][15][16] causes male-to-female phenotypic sex reversal while Sox9 gain-of-function, such as duplication of the SOX9 locus in humans [17,18] and Sryindependent upregulation of Sox9 in the fetal gonadal ridges of Wt1-Sox9 transgenic mice, causes testis formation in XX individuals [19]. The role of Sox9 in sex determination has mostly been studied in the context of two X chromosomes and focused on the period during fetal development when the sex determination takes place.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, Lee et al. () suggested that during paternal meiosis, 10% of the cases do not carry Y chromosome ( SRY negative). Interestingly, based on our study, the rate of the negative SRY in Iranian population was determined to be approximately 9.7%.…”
Section: Discussionmentioning
confidence: 95%
“…In most sex reversal cases, SRY is present ( SRY positive), while 10% of them do not carry this region on their X chromosome ( SRY negative). They show hypospadias, undescended testes or various degrees of inadequate virilisation in the external genitalia (Ergun‐Longmire et al., ; Lee, Ko, Shin, & Yang, ). The transcription of SOX9 (SRY‐box 9 gene) is enhanced in the genital ridge by SRY .…”
Section: Introductionmentioning
confidence: 99%
“…The study suggested that the extra dose of SOX9 is sufficient to initiate testis differentiation in the absence of SRY ; however, the gonadal histology was not described. A recent case of a boy with normal genitalia has also been reported with a SOX9 duplication [Lee et al, 2014].…”
Section: Mechanisms Underlying Testis Differentiation In Sry -Negativmentioning
confidence: 99%